Radiological progression of rheumatoid arthritis in renal transplant recipients. - Lamminen, A (1985)
Radiological progression of rheumatoid arthritis (RA) was evaluated retrospectively in eight patients with amyloidosis secondary to classical or definite RA and successful renal transplantation. Wrist joints, metacarpophalangeal, proximal interphalangeal, and metatarsophalangeal joints were graded on a scale from 0 to 5. The annual progression rate was calculated separately for the time before and after transplantation. A slight acceleration of the progression was observed after transplantation and is assumed to be due to activation of the rheumatoid disease when the azotaemia was corrected.